Awareness of female condoms and failures reported with two different types in China. Issue 2 (February 2015) - Wang, Xianmi; Xi, Maomao; Zhang, Lifeng; Jia, Lili; Wang, Yan; Cheng, Yimin
Abstract Objective To explore knowledge and use of female condoms in China, and to compare four modes of failure between the Phoenurse female condom (PFC) and the second-generation Femidom female condom (FC2). Methods In a randomized, crossover trial, sexually active women aged 20–49 years who attended a family planning service in Qingdao, China, were recruited between April and October, 2013. A computer-generated randomized sequence was used to assign participants (1:1) to group A (used 10 PFCs followed by 10 FC2s) or group B (used 10 FC2s followed by 10 PFCs). Study investigators and participants were masked to allocation. Participants completed questionnaires at baseline and after using the two types of FCs. They also kept coital logs. Results At baseline, 30 (10.3%) of 290 participants understood female condoms, but only 1 (0.3%) had ever used one. Total failure rates were 3.6% (420/11 578) and 2.3% (265/11 594) for PFC and FC2, respectively (P < 0.001). Slippage was the most common form of failure, affecting 6.9% of PFC uses and 5.0% of FC2 uses. Breakage, misdirection, and slippage were significantly more common with the PFC than with the FC2 (P ≤ 0.002). Conclusion Understanding of female condoms is poor in China. Failure is more common with the PFC than with the FC2.